2022
DOI: 10.1098/rsta.2021.0140
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic impacts of energy access through off-grid systems in rural communities: a case study of southwest Nigeria

Abstract: The development of resilient energy systems is important for sustainable cities and communities. However, in countries with insufficient national energy supply, electricity distributors rarely consider remote communities due to their distant settlement, low electricity demand and poor payment capabilities. The United Nations has set a goal to deliver universal energy access by 2030; hence, it has become imperative to deploy clean and affordable off-grid mini-grid solutions to previously abandoned communities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Similar studies that support the conclusion that it makes economic sense to use RE for rural electrification in WA are in Refs. [ 10 , 66 , [68] , [69] , [70] , [71] , [72] ].…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies that support the conclusion that it makes economic sense to use RE for rural electrification in WA are in Refs. [ 10 , 66 , [68] , [69] , [70] , [71] , [72] ].…”
Section: Results and Analysismentioning
confidence: 99%
“…Babalola et al (2022) attempted to find evidence of how electricity from mini-grids influenced productive activities. They used descriptive statistics to assess the impact of an 85 kW solar hybrid mini-grid on the socio-economic growth of a remote village in Nigeria [ 93 ]. The results showed that the mini-grid brought innovative businesses such as commercial electric motorcycles for transportation to the village.…”
Section: Results and Analysismentioning
confidence: 99%
“…Off-grid renewable energy solutions are viewed as revolutionary because they give rural people all over the world access to safe, cheap electricity, therefore enhancing their social and economic standing [13]. According to Babalola et al [14], mini-gridswhich are characterised as independent power systems or networked distributed energy resources-are essential for fostering micro and small businesses and helping rural communities realise their full economic potential. To guarantee a cheap and dependable supply of power in underserved areas, the assessment highlights the significance of integrating communities in the mini-grid design process, creating norms and regulations by governments, and striking a balance between the interests of investors, communities, and governments.…”
Section: The Lack Of Power Supplymentioning
confidence: 99%
“…The prevailing studies predominantly focus on technical and economic aspects, neglecting the quantification of social ramifications [25][26][27][28]. A recent study in the Gbamu Gbamu village in Nigeria uses statistical tests to measure the financial impact of RMGs on local businesses using predominantly economic factors including gender, marital status, household size, age, education level, years of business establishment, hours of operation, building tenure, capital source, number of employees, generator ownership, and the days of operation [29].…”
Section: Introductionmentioning
confidence: 99%